Pelatihan Pembuatan Filtrasi Sederhana Karang Taruna Miftahul Jannah Dalam Membangun Kesehatan Lingkungan Sungai - Alawiyah, Tuti; Yuwindry, Iwan; Nurhayati, Nurhayati (UKInstitute, 2023)
Sasirangan liquid waste as a form of the textile industry has a high polluting power so it does not meet the requirements to be discharged into the environment before being processed. Sasirangan wastewater pollution parameters exceed the textile industry wastewater quality standards. Until now, in the Sungai Jingah Village there is no institutional team structure to overcome these weaknesses in waste management. Therefore, we carry out a program that can solve these problems, namely by optimizing the function of the Miftahul Jannah Youth Organization, which is domiciled in the local environment, namely the Partner Assistance Program with the theme